EVALUATION OF THE COURSE CONTENT OF THE NURSING DEGREE BY ITS GRADUATES - Débora Dada Martinéli; Camila Rumi de Moura; Claudia Bernardi Cesarino; Lúcia Marinilza Beccaria; Maria Helena Pinto; Vânia Del Arco Paschoal (Universidade Federal do Paraná, 2011)
A case study carried out with the objective of verifying the opinion of graduates of the degree in Nursing on the contribution of two different curriculums to their professional formation. Data was collected in November and December 2009, using a questionnaire with open and closed questions, sent either by email or registered post to the 231 former students of the 'minimum' curriculum of 2005 and 2005, and the present curriculum of 2006 and 2007. Of the 231 former students, 39.4% replied, the majority of whom were pursuing a post-graduate qualification and working in hospitals. They considered the systematization of nursing assistance to be essential content, and they evaluated the course as flexible and with integrated disciplines. The following were noted: changes in how students conceived of subjects, pedagogical practices, greater integration of basic disciplines with professionalizing activities, an increase in research activities and continuing professional development, and greater focus on health promotion and the prevention of disease. Nevertheless, the changes were not sufficient to meet the demands of public policy.